Integrated Approach to Investigate the Potential of Asphalt/Tar Sand on Buton Island, Indonesia - Bambang Widarsono; Djoko Sunarjanto; Tri Muji Susantoro; Suliantara Suliantara; Herru L Setiawan; Panca Wahyudi; Sugihardjo Sugihardjo; Mohamad Romli; Diana Dwiyanarti (Scientific Contributions Oil and Gas, 2023)
Buton island as a potential area for conventional oil and gas, as well as asphalt/bitumen has long been the target of evaluation aimed at exploiting this potential, although to date no economic exploitation has been implemented. In this study, the potential of Buton asphalt/bitumen with mineable and in situ (non-mineable) status was studied and evaluated. In this study, qualitative and quantitative analysis have been carried out from Landsat 8 and Shuttle Radar Topography Mission (SRTM) data with the aim of identifying the presence of active faults and gravity due to orogenic processes. The lineament density pattern shows a general direction of NE-SW to NNW-SSE. The lineament process between satellite image data and gravity surveys helps efforts to identify the distribution of asphalt on Buton Island. Through combining distribution patterns of the Sampolakosa, Tondo, and Winto Formations, contain asphalt/bitumen, the study produces distribution of asphalt/bitumen accumulation in the region, both in surface/mineable and in situ categories. The 'best estimate' reserves obtained are 786.6 million barrels and 46 million barrels, respectively for asphalt/bitumen surface/mineable reserves and in situ/non-mineable reserves. It is hoped that this information regarding the potential/reserves of asphalt/bitumen on Buton Island may support efforts to exploit it